Using cluster segmentation method for the design of DSS module - Чорний, Сергій Григорович; Райко, Галина Олександрівна; Козуб, Наталія Олександрівна; Ігнатенко, Галина Анатоліївна (Eastern-European Journal of Enterprise Technologies, 2010)
The possibilities of using the segmentation were considered for designing of module an integrated information system for regional development. Using Oracle and OLAP technologies was suggested, as a mutual component of regional information system.